2008
DOI: 10.1124/jpet.108.142034
|View full text |Cite
|
Sign up to set email alerts
|

Late, but Not Early, Inhibition of Soluble Guanylate Cyclase Decreases Mortality in a Rat Sepsis Model

Abstract: Overproduction of nitric oxide and activation of soluble guanylate cyclase (sGC) are important in sepsis-induced hypotension and hyporesponsiveness to vasoconstrictors. A time course of the expression and activity of sGC in a sepsis model [cecal ligation and puncture (CLP)] was evaluated in rats. Soluble GC ␣-1 and ␤-1 subunit mRNA levels increased in the lungs, but not in the aorta. However, in both tissues, the protein levels increased 24 h after sepsis and remained high for up to 48 h. Sodium nitroprusside-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…One of these selective agents is methylene blue, which may restore vascular tone and improve tissue perfusion. There are multiple experimental models of septic shock that support the use of methylene blue in the treatment of refractory distributive shock [70][71][72][73][74][75][76]. The majority of clinical data on the use of methylene blue for such therapy is observational with case reports and small observational studies, but there are also small controlled clinical trials [77][78][79][80][81][82].…”
Section: The No-cgmp Pathway In Anaphylaxis and The Role Of Methylenementioning
confidence: 99%
“…One of these selective agents is methylene blue, which may restore vascular tone and improve tissue perfusion. There are multiple experimental models of septic shock that support the use of methylene blue in the treatment of refractory distributive shock [70][71][72][73][74][75][76]. The majority of clinical data on the use of methylene blue for such therapy is observational with case reports and small observational studies, but there are also small controlled clinical trials [77][78][79][80][81][82].…”
Section: The No-cgmp Pathway In Anaphylaxis and The Role Of Methylenementioning
confidence: 99%
“…These dual effects of cGMP appear to depend, at least in part, on the timing of sGC inhibition: cGMP might be detrimental in one phase of inflammatory shock but protective in another (15,16). Alternatively, it cannot be excluded that the source of cGMP (sGC␣ 1 ␤ 1 or sGC␣ 1 ␤ 2 ) determines its impact on cardiac function.…”
mentioning
confidence: 99%
“…Our group recently showed that the increase of NOS-1 expression during sepsis plays a role in hypotension and vascular dysfunction observed in this condition [16], since it is time-matched with the expression of the most important NO target, soluble guanylate cyclase, in vessels [52]. The up-regulation of both c-NOS has also been shown in different tissues of sepsis-bearing animals [52,53].…”
Section: Discussionmentioning
confidence: 96%